Promoting Religious Moderation through Islamic Education Studies Amid the Covid-19 Pandemic in Bima - Azhar Azhar (UIN Mataram, 2022)
This article aims to discuss how religious moderation is promoted through Islamic Education Studies (Pendidikan Agama Islam / PAI) in the midst of the COVID-19 pandemic in Bima. This research uses a qualitative approach with a case study method. Researchers conducted interviews with Islamic Education Studies teachers and some students at Public Junior High School 1 Bima. The results showed that in promoting religious moderation in the midst of the COVID-19 pandemic, Islamic Education Studies teachers at Public Junior High School 1 Bima used several religious attitudes, they are as follow: justice (‘adalah) attitude, tolerance (tasamuh) attitude, balance (tawazun) attitude, diversity (tanawwu’) attitude and exemplary (uswah) attitude. Keywords: Religious Moderation, Islamic Education Studies, the COVID-19 Pandemic Abstrak: Artikel ini bertujuan untuk membahas bagaimana moderasi beragama dipromosikan lewat pembelajaran Pendidikan Agama Islam di tengah pandemi COVID-19 di Bima. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Peneliti melakukan wawancara kepada para guru PAI dan beberapa siswa di SMP Negeri 1 Bima. Hasil penelitian menunjukan bahwa dalam mempromosikan moderasi beragama di tengah pandemi COVID-19, guru PAI di SMP Negeri 1 Bima menggunakan beberapa sikap keberagamaan, antara lain: Sikap adil (‘adalah), sikap toleransi (tasamuh), sikap keseimbangan (tawazun), sikap keberagaman (tanawwu’) dan sikap keteladanan (uswah).